Peru and dependent multilateralism - Olano Alor, Aldo (2016)
This article reviews the internal dynamics of the foreign policies adopted by Peru in its attempt to integrate into the international economy. The authors consider that, paradoxically, current Peruvian policy is not new, but marked by the “deepening of historic multilateralism”, and a new vision of the competition between old and new powers at a global scale. The authors state that the supposedly opposed policies of regionalism and multilateralism, instead could be reconciled in the practice of Peruvian international economic relations.